Pengujian Efek Proteksi Jus Tomat (Solanum Lycopersicum (L.)) Terhadap Fungsi Ginjal Tikus Yang Diinduksi Parasetamol - Angelia Vega; Asyrun Alkhairi Lubis; Muhammad Yunus (Universitas Muhammadiyah Manado, 2025)
Excessive doses of paracetamol can cause nephrotoxicity due to accumulation of NAPQI and oxidative stress, which damages the proximal tubules of the kidney. Tomato (Solanum tomato L.) which is rich in lycopene has the potential to prevent this damage through its antioxidant activity. This experimental study used a posttest-only control group design with 25 white rats (Rattus norvegicus) divided into 5 groups: positive control, negative control, and three treatment groups. The mice were induced with toxic doses of paracetamol, while the treatment group was given tomato juice. Evaluation is carried out through measurement of plasma creatinine and renal histopathological analysis. The results showed that toxic doses of paracetamol (250 mg/kgBW) increased creatinine levels and relative kidney weight, which indicated acute kidney damage. Giving high doses of tomato juice (800 mg/kgBW) was most effective in reducing creatinine levels and protecting kidney tissue compared to lower doses. Administration of paracetamol 250 mg/kgBW caused kidney damage which was characterized by an increase in creatinine and relative kidney weight. Tomato juice at a dose of 800 mg/kgBW provided the best protective effect by reducing creatinine levels close to the positive control. These results demonstrate the potential of tomato juice as a protective agent against paracetamol-induced kidney damage.